2021
DOI: 10.3390/microorganisms9102007
|View full text |Cite
|
Sign up to set email alerts
|

Serra da Estrela PDO Cheese Microbiome as Revealed by Next Generation Sequencing

Abstract: Serra da Estrela PDO cheese is the oldest traditional cheese manufactured in Portugal. In this work, its microbiome as well as the main raw materials used in cheese production, raw ewes’ milk and thistle flowers (Cynara cardunculus L.), were characterized using next generation sequencing. Samples were accordingly retrieved from a local producer over two consecutive production campaigns and at different time periods within each campaign. The bacterial and fungi communities associated with each matrix were acces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 88 publications
(173 reference statements)
2
6
0
Order By: Relevance
“…Further research is needed to identify the causes of this high variation of SPZ viability in this breed after the freeze-thawing cycle. However, we have showed that SPZ cryopreservation is the main factor for a significant decrease in semen quality, which is normal and is in accordance to literature [27][28][29]. However, some Portuguese breeds have got good IM like some improved European breeds that trade semen doses at good prices [28].…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Further research is needed to identify the causes of this high variation of SPZ viability in this breed after the freeze-thawing cycle. However, we have showed that SPZ cryopreservation is the main factor for a significant decrease in semen quality, which is normal and is in accordance to literature [27][28][29]. However, some Portuguese breeds have got good IM like some improved European breeds that trade semen doses at good prices [28].…”
Section: Discussionsupporting
confidence: 87%
“…A 36.1% decrease between fresh and thawed semen was observed in Serra da Estrela rams, which is one of the breeds with higher SPZ viability in the fresh semen (71.2%). This important breed produces the oldest traditional cheese manufactured in Portugal, Serra da Estrela Cheese (PDO) [28]. Nevertheless, the alive SPZ (45.5%) after thawing for this breed, remains similar to all the others breeds.…”
Section: Discussionmentioning
confidence: 92%
“…The antimicrobial activity of sorghum leaf extract (Akogou et al, 2018 ; Schnur et al, 2021 ) and further processing, such as drying, may have favored Streptococcus spp. Contrary to the cheese types produced worldwide from cow milk through natural fermentation, L. lactis and L. mesenteroides (Delcenserie et al, 2014 ; Shangpliang et al, 2017 ; Rocha et al, 2021 ; Sun and D'Amico, 2021 ; Zhang et al, 2021 ) were not predominant in Wagashi cheese, while Streptococcus spp. dominated.…”
Section: Discussionmentioning
confidence: 93%
“…Studies of the microbiota of PDO "Serra da Estrela" cheeses are scarce as it is impossible to make comparisons between them; they only allow for recognizing the presence of the major groups, which are, Lactococci, Lactobacilli and Enterococci [12]. Thus, studies using metagenomics of the populations of LAB present in "Serra da Estrela" cheese showed the presence of Lactococcus, Lactobacillus and Leuconostoc but also revealed a great variability between populations [41]. In these cases, the presence of L. plantarum and Le.…”
Section: Discussionmentioning
confidence: 99%